RESEPSI PENONTON TERHADAP KONTEN REVIEW SKINCARE DALAM AKUN TIKTOK @drrichardlee: Studi Analisis Resepsi Penonton Terhadap Konten Review Skincare dalam Tiktok @drrichardlee - Reyhana Savira; Saifuddin Zuhri (Linimasa : Jurnal Ilmu Komunikasi, 2022)
This research is motivated by a skincare review content on @drrichardlee tiktok account. The stereotype of beautiful white skin in Indonesia has caused many people to want their skin to look white by using various methods, including using a whitening cream containing mercury and hydroquinone. Doctor Richard created skincare review content to disassemble the ingredients in skincare circulating in the community.The review content caused controversy, and make pros and cons in public. because the content can cause a bankruptcy to some business. However, the content is also considered as educating content for public. This study focuses on how @drrichardlee's tiktok audience receives media text messages in the video review on the @drrichardlee tiktok account review entitled Skincare Daviena, Review Krim Viral Laris Manis, and Review Krim Temulawak. This study uses qualitative research method with a reception analysis study of the encoding-decoding theory from Stuart Hall. The researcher used 6 informant to answer the research problems. The results of this study show that there are different interpretations by the informants in understanding the review videos. The results are influenced by field of experience and frame of reference of each informants. 2 informants are in the dominant hegemonic category, 4 informants are categorized in the negotiated reading position, and no informant in the oppositional reading position.